Penerapan Manajemen Konflik Dalam Mengurangi Kenakalan Remaja Di SMK Negeri 1 Glagah Banyuwangi - Azizah, Nadiva Afni; Adhani, Amanda Sekar Hari; Hidayatullah, Rohmat; Fitriana, Ani Qotuz Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
Family is an initial need in the period of growth and development of children, the most important thing in the child's growth period is that there must be supervision from parents. Children who in their growth period do not have the role of family or parents can be a trigger for children to become naughty, in order to get attention from others. This study aims to find out the application of conflict management in reducing delinquency as well as minimizing and resolving juvenile delinquency conflicts at SMK Negeri 1 Glagah, Banyuwangi. The research method used is descriptive qualitative which is a research stage that can produce descriptive data in the form of written or spoken words from people as well as observable behavior, and the approach of this research is directed at the background and individuals holistically (Abdussamad, n.d. ). Research that has been conducted at SMK Negeri 1 Glagah shows that parents have an important role in the growth and development of children, both physically and psychologically. This study also found that a broken home can be a trigger factor for juvenile delinquency in schools. Therefore, the application of conflict management in terms of reducing delinquency that occurs certainly has a very positive contribution, because by applying good communication a conflict can be resolved without any misunderstandings.